Progression of Hip Dysplasia in Mucopolysaccharidosis Type I Hurler After Successful Hematopoietic Stem Cell Transplantation. (2nd March 2016) - Langereis, Eveline J.; den Os, Matthijs M.; Breen, Catherine; Jones, Simon A.; Knaven, Olga C.; Mercer, Jean; Miller, Weston P.; Kelly, Paula M.; Kennedy, Jim; Ketterl, Tyler G.; O'Meara, Anne; Orchard, Paul J.; et al.
Abstract : Background: Dysostosis multiplex contributes substantially to morbidity in patients with Hurler syndrome (mucopolysaccharidosis type I Hurler phenotype [MPS I-H]), even after successful hematopoietic stem cell transplantation (HSCT). One of the hallmarks of dysostosis multiplex in MPS I-H is hip dysplasia, which often requires surgical intervention. We sought to describe in detail the course of hip dysplasia in this group of patients, as assessed by radiographic analysis, and to identify potential outcome predictors. Methods: Longitudinal data were obtained from digitally scored pelvic radiographs of patients with MPS I-H using OrthoGon software for parameters including, but not limited to, the acetabular index, migration percentage, Smith ratio, and neck-shaft angle. Scoring was performed independently by two blinded observers. Additional information on genotype, enzyme replacement therapy pre-HSCT, donor chimerism, and enzyme activity post-HSCT were obtained. General trends and potential correlations were calculated with mixed-model statistics. Results: Fifty-two patients (192 radiographs) were included in this analysis. Intraobserver and interobserver variation analysis showed an intraclass correlation coefficient ranging from 0.78 to 1.00. Among the twenty-one patients with follow-up beyond the age of five years, the acetabular index was in the range of severe hip dysplasia in up to 86% of the patients. Severe coxa valga was seen in 91% of the patients. Lateral and superior femoral displacement were highly prevalent, with the migration percentage outside the reference range in up to 96% of the patients. Finally, anterior pelvic tilt increased with age (p = 0.001). No correlations were identified between clinical parameters and radiographic findings. Conclusions: Our study shows that progressive acetabular dysplasia as well as coxa valga and hip displacement are highly prevalent and progressive over time in patients with MPS I-H, despite successful HSCT. These data may provide essential natural history determinations for the assessment of efficacy of new therapeutic strategies aimed at improving skeletal outcomes in patients with MPS I-H. Level of Evidence: PrognosticLevel IV . See Instructions for Authors for a complete description of levels of evidence.